Ripening and cooking processes influence the carotenoid content in bananas and plantains (Musa spp.) - Borges, C. [UNESP]; Minatel, I. O. [UNESP]; Amorim, E. P.; Belin, M. A. F. [UNESP]; Gomez-Gomez, H. A.; Correa, C. R. [UNESP]; Lima, G. P. P. [UNESP] (Elsevier B.V., 2019)
In bananas, the major carotenoids are alpha- and beta-carotene, which give this fruit great potential in biofortification programs. The carotenoid content in pulp and peel of 22 banana and plantain genotypes was determined in order to evaluate the impact of ripening on the carotenoid content as well as its retention after different thermal processes. Fruits were ripened at stage 2 (green), 5 (yellow) and 7 (yellow with dark spots). The provitamin A content (pVACs) varied from 20.8 ('Muisa Tia' stg 7) to 6341.5 mu g/100 g f.w. ('Samura B' stg 5). High quantities were identified in plantains, which have yellow pulp, a phenotypic characteristic that can indicate the quantity of pVACs in Musa spp. fruit. The 'Samura B' plantain showed the highest pVACs (6341.5 mu g/100 g f.w.) and trans-beta-carotene (5220.0 mu g/100 g f.w.) content in pulp, especially when compared to the 'D'Angola' plantain (pVACs: 3214.0 mu g/100 g f.w.), the most common in Brazil, and with the dessert cultivar from the Cavendish subgroup ('Grand Naine' - pVACs: 230.6 mu g/100 g f.w.), the most consumed worldwide. The highest pVACs quantity was verified in the ripe fruit (stg 5), decreasing during the fruit ripening (stg 7). In the peels, lutein was the majority compost, with contents higher than the pulp. The highest lutein content was identified in the green fruit peels from the 'Terra Ana Branca' cultivar (1602.1 mu g/100 g d.w.), almost ten times higher than the content found in the pulp of the same cultivar. However, the pulp of all the cultivars showed superior values of pVACs, trans-beta-carotene and trans-alpha-carotene, mainly in the ripe stage 5. The plantain `Sarnura B' has nutritional and/or functional properties, and its promotion/incorporation in existing agricultural systems is of interest for use in biofortification programs. In addition, thermal processing can improve bioactive compounds release and increase the functional and nutritional value of the Musa spp. fruit, mainly by boiling, which should be the favorite in domestic preparations, regardless of the cultivar used.
Keywords: Provitamin A; beta-Carotene; Boiling; Lutein